METAFORA PADA LIRIK LAGU ENKA - Denny Alisha Utami; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study discusses the types of categories metaphors contained in the lyrics of Enka Song. The purpose of this study is to determine the type of category metaphors on the lyrics of Enka Song. This is quantitative study with descriptive method. The result of study found fifteen types of metaphor anthropormic, animal, and from concert to abstract. The type of sinaestetic being are not found in this study.Key Word : Metaphors, Lyric, Enka Song